Restriction of intramolecular torsion induces abnormal blue-shifted fluorescence in the aggregate state. (May 2022) - Yin, Hang; Li, Bo; Zhao, Xin; Liu, Yuliang; Shi, Ying; Ding, Dajun
Abstract: The aggregation-induced emission (AIE) effect and corresponding restriction of intramolecular motions strategy are important mechanisms for regulating the performance of novel organic light-emitting diode materials and constituent molecules, such as emission intensity and peak position. Nevertheless, molecules in the aggregate state usually yield a red-shifted fluorescence due to the π-π interaction enhancement. Here, we report a blue-shifted fluorescence mechanism induced by the restriction of intramolecular torsion in the aggregate state for an interesting excited-state intramolecular proton transfer fluorophore. A combined experimental and theoretical method is performed to investigate the excited state dynamics of the molecules in solvent and the aggregate state respectively. Multiple regression analysis reveals that the changes of reorganization energy caused by AIE effect induce the blue-shifted fluorescence. These findings contribute in several ways to our understanding of the AIE effect, and provide a new strategy to regulate the emission performance of AIE materials. Graphical abstract: Image 1 Highlights: Two derivatives of dibenzothiazolylphenol, the OMe and OPr, exhibit different luminescence mechanism upon aggregation. The abnormal blue-shifted fluorescence phenomenon of the OPr arises from the restriction of intramolecular torsion. The restriction of intramolecular torsion causes an uncommonly decreasing of ESIPT rate for the OPr in the aggregate state.